The Full‐Scale Implementation of an Innovative Biological Ammonia Treatment Process. Issue 12 (1st December 2015) - Lytle, Darren A.; Williams, Dan; Muhlen, Christy; Pham, Maily; Kelty, Keith; Wildman, Matthew; Lang, Glenn; Wilcox, Mitch; Kohne, Melissa
Abstract : Across the United States, high levels of ammonia in drinking water sources can be found. Although ammonia in water does not pose a direct health concern, ammonia nitrification can cause a number of issues and reduce the effectiveness of some treatment processes. An innovative biological ammonia‐removal drinking water treatment process was developed and, after the success of a pilot study, a full‐scale treatment system using the process was built in a small Iowa community. The treatment plant included a unique aeration contactor design that is able to consistently reduce ammonia from 3.3 mg of nitrogen/L to nearly nondetectable after a biofilm acclimation period. Close system monitoring was performed to avoid excess nitrite release during acclimation, and phosphate was added to enhance biological activity on the basis of pilot study findings. The treatment system is robust, reliable, and relatively simple to operate. The operations and effectiveness of the treatment plant were documented in the study.